Right-hemisphere coherence to speech at pre-reading stages predicts reading performance one year later. Issue 2 (17th February 2022) - Ríos-López, Paula; Molinaro, Nicola; Bourguignon, Mathieu; Lallier, Marie
ABSTRACT: Neural entrainment to the low-frequency modulations of speech might contribute significantly to reading acquisition. Still, no previous study has actually attempted to establish a longitudinal link between them. The present study tested Basque-speaking children twice: once before reading was formally instructed ( t 1 ; 5–6 years old) and once after they had received a full school year of reading instruction ( t 2 ; 6–7 years old). At t 1, speech-brain coherence was recorded via EEG. At t 2, in addition to the coherence measure, reading performance was assessed. Our results show that children with larger pre-reading delta-band (<1 Hz) speech-brain coherence at right sites of the scalp performed better in the reading tasks one year later. Overall, our results provide preliminary support for a relevant contribution of right-hemisphere speech-brain coherence to successful reading development and point towards pre-reading neural coherence indexes as useful tools for the early detection of developmental reading disorders.